17 Inflammatory Spinal Disorders (Video Atlas of Spine Surgery, 2020)
Noninfectious inflammatory spinal diseases constitute a heterogeneous body of conditions that are frequently encountered by spine surgeons. While the need for surgical treatment of such diseases has diminished with the development of improved medical therapies, understanding the appropriate management of these conditions is important to prevent patients from having gross deformity and/or neurological deficits in terminal stages of their disease. Seronegative spondyloarthropathies, including ankylosing spondylitis (AS), have the potential to develop severe kyphotic deformities, requiring horizontal gaze assessments and, potentially, spinal osteotomy to restore sagittal balance. Enteropathic arthritides, reactive spondyloarthritis, psoriatic arthritis (PA), and other uncommon syndromes are recognized variations of spondyloarthritis. Rheumatoid arthritis (RA) is a common condition that has the potential to affect the spine, most often the upper and subaxial cervical spine, with uncommon involvement of the lumbar spine. Hypertrophic spine arthropathies include diffuse idiopathic skeletal hyperostosis (DISH) and Paget’s disease. Arthropathic spine syndromes include those in which the predominant disease involves spinal ligament ossification, such as Ossification of the Posterior Longitudinal Ligament (OPLL) and Ossification of the Yellow Ligament (OYL). Though these conditions present with distinct pathophysiologies, many patients share similar signs and symptoms and pose challenges in making a timely diagnosis, pursuing appropriate surgical management, and coordinating care with other medical providers.
Keywords: spondyloarthritis; spondyloarthropathy; ankylosing spondylitis; rheumatoid arthritis; DISH; Paget’s disease; OPLL; HLA-B27